P.134L: Late News Poster: Resolution Limits for Smartphones — Video Playback. Issue 1 (1st July 2013) - Spencer, Lee; Iacoponi, Julian; Shah, Sunay; Cairns, Graham
Abstract This study aims to determine an upper discernible resolution limit for smartphone displays showing video. A range of resolutions varying from 150–600 PPI were evaluated by 43 subjects at 300mm equivalent distance. Results of the study conclusively show users can discriminate between 450 and 600 PPI video playback.